Klong Yuen - Klong Lorn: Beating Techniques of Mangkala Folk Philosophers in Phitsanulok - Teelakun, Supachai (Journal of Humanities and Social Sciences Suratthani Rajabhat University, 2023)
This research article presents a part of the research entitled " Development in the Teaching Kits of Beating Klong Yuen-Klong Lorn.” This research aimed to study techniques for Klong Yuen and Klong Lorn by Mangkala folk local wisdom scholars Mr.Tao Meenak and Mr. Prayoad Lookplub. Data is collected using research and development methodologies: observation and interview. Two purposive informants were selected from Mangkala Folk local wisdom scholars. The research findings were presented using an analytical description. The findings of this research showed that there are 4 techniques to beat Klong Yuen – Klong Lorn in Phisanulok: 1) handling drumsticks, 2) positioning hands, 3) composing various sounds, and 4) beating the points of Klong Yuen – Klong Lorn with the similar techniques. There are 4 Klong Yuen and 3 Klong Lorn composing sounds. The different sound is named Nued or Ting 2, which is caused by the development to be easy to understand according to the opinion of Mangkha local wisdom scholars in each individual.